Unified Resource Allocation Framework for the Edge Intelligence-Enabled Metaverse - Ng, Wei Chong; Yang Bryan Lim, Wei; Ng, Jer Shyuan; Xiong, Zehui; Niyato, Dusit; Miao, Chunyan (IEEE International Conference on Communications (2003), 2022)
Dubbed as the next-generation Internet, the meta-verse is a virtual world that allows users to interact with each other or objects in real-time using their avatars. The metaverse is envisioned to support novel ecosystems of service provision in an immersive environment brought about by an intersection of the virtual and physical worlds. The native AI systems in metaverse will personalized user experience over time and shape the experience in a scalable, seamless, and synchronous way. However, the metaverse is characterized by diverse resource types amid a highly dynamic demand environment. In this paper, we propose the case study of virtual education in the metaverse and address the unified resource allocation problem amid stochastic user demand. We propose a stochastic optimal resource allocation scheme (SORAS) based on stochastic integer programming with the objective of minimizing the cost of the virtual service provider. The simulation results show that SORAS can minimize the cost of the virtual service provider while accounting for the users' demands uncertainty.